An innovative computational algorithm for modelling technical readiness coefficient: A case study in automotive industry - Szkutnik-Rogoż, Joanna; Małachowski, Jerzy; Ziołkowski, Jarosław (Computers & industrial engineering, 2023)
Modelling technical availability is particularly important in systems characterised by randomness in the occurrence of tasks. The aim of the article was to develop an innovative solution using the Laplace transform and the R programming language in the form of an algorithm designed to determine a reliability measure, the technical readiness coefficient. First, the literature on the most important theorems and definitions concerning the theory of reliability was reviewed to develop assumptions and a mathematical model of the actual process of using means of transport. The subject of the research, along with the availability of actual numerical data used for calculations and analyses were presented. An algorithm based on the Laplace transform was proposed to evaluate the reliability of the system. Furthermore, the sensitivity analysis of the model was performed and the results were discussed to identify final conclusions and directions for future research. The results show that the exploitation process of the vehicle fleet studied was correctly organised and that the proposed algorithm eliminates the need to perform complex calculations using traditional methods and enables the visualisation of the achieved results. Additionally, the algorithm is universal and can be used to determine both the functional and numerical reliability characteristics of any technical object. Moreover, this solution is free of charge, and its implementation requires only the installation of the RStudio editor (version 1.4.1106). •An innovative algorithm using the R programming language was proposed.•Universality of the algorithm ensures modelling the readiness of any objects.•The algorithm eliminates complex calculations using traditional methods.•The proposed algorithm enables the visualisation of results.